Association of arbuscular mycorrhizal fungi (AMF) with Brachiaria precumbens (Poaceae) in tailing and its potential to increase the growth of maize (Zea mays) - SUHARNO SUHARNO; ENDANG SUTARININGSIH SOETARTO; RETNO PENI SANCAYANINGSIH; RINA SRI KASIAMDARI (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Suharno, Soetarto ES, Sancayaningsih RP, Kasiamdari RS.2017. Association of arbuscular mycorrhizal fungi (AMF) with Brachiaria precumbens (Poaceae) in tailing and its potential to increase the growth of maize (Zea mays).Biodiversitas 18: 433-441.The role of Arbuscular Mycorrhizal Fungi (AMF) in the process of rehabilitation of degraded land is very important, including the handling of sand tailings. In the rehabilitation process, utilizing the AMF isolates from the tailings area will be easier to adapt to the habitat that will be rehabilitated. The purpose of this study was to determine AMF that associated with Brachiaria precumbens (Poaceae) derived from the tailings area in Timika, Papua, and its potential to the growth of maize (Zea mays). The methods used to determine the presence of AMF were a survey and wet sieving methods, while the calculation of percent colonization was done by slide method. The compatibility test and effectiveness of AMF inoculation on the maize growth were conducted by completely randomized design (CRD) with 4 treatments: M0: control (without mycorrhiza); M1: Clariodeoglomus etunicatum BGR; M2: C. lamellosum L1A01S; M3: C. etunicatum L3A12D each with eight replications. The results showed that the presence of the AMF in the rhizosphere of B. precumbens was found in the tailings deposition area Modified Ajkwa Deposition Area (ModADA) of a gold mine in Timika. AMF percent colonization at the root reached 73.3%, while the number of spores in the rhizosphere was 8-25 per 10 g samples of soil and increased to reach an average of 49.6 spores per 10 g soil samples by trap methods. Based on the morphological identification, AMF found in the B. precumbens rhizosphere were identified as genus Glomus, Scutellospora, Acaulospora, and Claroideoglomus, whereas based on molecular identification, two isolates (L1A01S and L3A12D) were identified as C. lamellosum L1A01S and C. etunicatum L1A12D. The compatibility test showed that the AMF was able to increase the growth of maize, and significantly affected plant height, leaf area, and relative growth rate. C. lamellosum L1A01S derived from the tailings had a better effect than C. etunicatum L3A12D and C. etunicatum BGR. Keywords: Arbuscular Mycorrhizal Fungi, Brachiaria precumbens, tailings, Timika, Zea mays